The progress of co-operation - Finlay, T.A. (Statistical and Social Inquiry Society of Ireland, 1897)
Everyone is familiar with the advantages of co-operation in industrial and commercial pursuits. What all treatises of Political Economy tell us as to the benefits of the Organisation of Industry and the Division of Labour is really nothing more than an exposition of the advantages of co-operation. But it is not in the sense of an organisation of industry that the term co-operation is now usually understuod. Since capital has come to play so important a part in the processes of production, co-operation has come to have a narrower signification. It signifies that particular kind of economic organisation by which those who are producers or consumers shall also be owners of the capital or the profits employed in, or arising out of, the production or the consumption. The continuous development of wealth production in the present century could hardly fail to suggest the idea of co-operation to thinkers who were concerned for the well-being of the masses, and to thinking individuals among the masses themselves, who were led to reflect on the hardships which the current methods of production and distribution created for the poor.
Read Tuesday, 1st December, 1896
Keywords: Cooperatives; Agricultural development; 314.15